Rhinovirus infection liberates planktonic bacteria from biofilm and increases chemokine responses in cystic fibrosis airway epithelial cells - Chattoraj, Sangbrita S. (2011)
BACKGROUND: Intermittent viral exacerbations in cystic fibrosis (CF) patients with chronic P. aeruginosa (PA) infection are associated with increased bacterial load. A few clinical studies suggest that rhinoviruses (RV) are associated with majority of viral-related exacerbations in CF and required prolonged intravenous antibiotic treatment. These observations imply that acute RV infection may increase lower respiratory symptoms by increasing planktonic bacterial load. However, the underlying mechanisms are not known. METHODS: Primary CF airway epithelial cells differentiated into mucociliary phenotype were infected with mucoid PA (MPA) followed by RV and examined for bacterial density, biofilm mass, levels of chemokines and hydrogen peroxide (H(2)O(2)). Requirement of dual oxidase 2 in RV-induced generation of H(2)O(2) in CF cells was assessed by using gene-specific siRNA. RESULTS: Super infection with RV increased chemokine responses in CF mucociliary-differentiated airway epithelial cells with pre-existing MPA infection in the form of biofilm. This was associated with the presence of planktonic bacteria at both the apical and basolateral epithelial cell surfaces. Further, RV-induced generation of H(2)O(2) via dual oxidase 2, a component of NADPH oxidase in CF cells was sufficient for dispersal of planktonic bacteria from biofilm. Inhibition of NADPH oxidase reduced bacterial transmigration across mucociliary-differentiated CF cells and IL-8 response in MPA and RV-infected cells. CONCLUSION: We show that acute infection with RV liberates planktonic bacteria from biofilm. Planktonic bacteria, which are more proinflammatory than their biofilm counterpart stimulates increased chemokine responses in CF airway epithelial cells, which in turn may contribute to pathogenesis of CF exacerbations.